Stacked cylindrical dielectric resonator antenna with metamaterial as a superstrate for enhancing the bandwidth and gain - Sahu B.; Aggarwal M.; Tripathi P.; Singh R. (My University, 2025)
A dual segment cylindrical dielectric resonator antenna with metamaterial superstrate is presented in this paper. The metamaterial cover acting as a converging lens is sharply increasing the gain of the proposed antenna and is also responsible for increasing the bandwidth. The proposed antenna is having a better impedance matching (less than -10 dB return loss) in a wide frequency band with a bandwidth of 2.12 GHz (8.49-10.61 GHz) and peak gain of 12.86 dB. The proposed antenna is presented with parametric analysis of some key parameters. Broadside radiation pattern is obtained without metamaterial, while directive radiation pattern with narrow beamwidth is obtained with metamaterial using as a superstrate. The gain characteristics of the proposed antenna are also presented. © 2013 IEEE.